2021
DOI: 10.1001/jamanetworkopen.2021.15991
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Measurable Residual Disease in Patients With Intermediate-Risk Acute Myeloid Leukemia and First Remission, Treatment, and Outcomes

Abstract: IMPORTANCE Measurable residual disease (MRD) is widely used as a therapy-stratification factor for acute myeloid leukemia (AML), but the association of dynamic MRD with postremission treatment (PRT) in patients with intermediate-risk AML (IR-AML) has not been well investigated. OBJECTIVE To investigate PRT choices based on dynamic MRD in patients with IR-AML. DESIGN, SETTING, AND PARTICIPANTS This cohort study examined 549 younger patients with de novo IR-AML in the South China Hematology Alliance database dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 53 publications
4
16
0
Order By: Relevance
“…Cytogenetic and molecular analyses were routinely performed at initial diagnosis [ 25 ]. After CR, MRD in bone marrow was assessed by eight-color multiparameter flow cytometry (MFC) after induction and each course of PRT and then at two-month intervals within the 1st year, three-month intervals within the 2nd year, four-month intervals within the 3rd year, and half-year intervals from the 4th to 5th year post-treatment [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Cytogenetic and molecular analyses were routinely performed at initial diagnosis [ 25 ]. After CR, MRD in bone marrow was assessed by eight-color multiparameter flow cytometry (MFC) after induction and each course of PRT and then at two-month intervals within the 1st year, three-month intervals within the 2nd year, four-month intervals within the 3rd year, and half-year intervals from the 4th to 5th year post-treatment [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…According to our practical guidelines, patients are generally scheduled for “3 + 7” induction therapy consisting of daunorubicin 60 mg/m2 or idarubicin 10–12 mg/m2 on days 1-3 and cytarabine 200 mg/m2 per day for 7 days. For those who failed to achieve CR after the first induction, a second induction consisting of daunorubicin 60 mg/m 2 or idarubicin 10 mg/m 2 per day on days 1–3 and cytarabine 2.0 g/m 2 twice daily on days 1–3 (“3 + 3” regimen), or the same regimen as the first induction was administered [ 25 ]. After CR, usually four courses of cytarabine-based consolidation chemotherapy, three courses of chemotherapy followed by auto-SCT, or two courses followed by allo-SCT were administered based on MRD status and donor availability.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a prospective trial comparing HID-HSCT and chemotherapy as consolidation therapy in 147 patients with int-risk AML CR1 in the absence of MSDs or URDs, HID-HSCT was an independent risk factor for a reduced cumulative incidence of relapse (CIR) (adjusted hazard ratio (HR) 0.161; p = 0.001), improved DFS (HR 0.360; p = 0.011) and overall survival (OS, HR 0.361, p = 0.017) [ 11 ]. Yu et al reported that in a multicenter study of 549 patients with int-risk AML, allo-HSCT had superior CIR, LFS and OS compared with chemotherapy in patients with any positive MRD after 1, 2, or 3 courses of chemotherapy [ 12 ].…”
Section: Indications and Timing Of Allo-hsctmentioning
confidence: 99%